Method for treating coffee waste, method for preparing composite material comprising same, and composite material comprising same

By pre-treating coffee grounds and coffee shells, including mixing with alkaline hydrogen peroxide and flocculant treatment, the problems of limited addition amount and insufficient mechanical properties of coffee waste in composite materials have been solved, achieving efficient resource utilization and performance improvement.

CN119306970APending Publication Date: 2025-01-14KINGS FLAIR TECHNOLOGY RESEARCH & DEVELOPMENT LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310867232.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-14
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The amount of coffee waste added to existing coffee waste polymer composites is limited, resulting in low resource recycling efficiency. Furthermore, coffee grounds are prone to sticking or agglomerating during processing, affecting the mechanical properties of the composites.

Method used

By mixing coffee grounds with hydrogen peroxide under alkaline conditions, followed by flocculant treatment and a water washing step, the pretreatment process of coffee grounds and coffee shells was optimized to remove organic groups and improve porosity, thus preparing a coffee waste polymer composite material that meets the performance requirements of composite materials.

Benefits of technology

The increased proportion of coffee waste in the composite material improved its mechanical properties and washability, reduced production costs, and made it suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119306970A_ABST
    Figure CN119306970A_ABST
Patent Text Reader

Abstract

The invention provides a method for treating coffee waste. The method comprises the following steps of: treating coffee grounds: mixing the coffee grounds with hydrogen peroxide under an alkaline condition to form a first mixture; the treated coffee grounds are obtained through the separation process. The invention also provides a method for making the coffee waste polymer composite material. The method comprises the step of treating the pressed coffee grounds.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a coffee waste treatment process and the use of the coffee waste treated by the present invention as a material to form a composite material with a polymer. In particular, the present invention relates to a coffee shell and coffee grounds treatment process and the use of the coffee shell and coffee grounds treated by the present invention as a material to form a composite material with a polymer such as polypropylene. Background Art

[0002] In recent years, with climate change and resource shortages becoming increasingly serious, sustainable consumption and production have become global concerns. Converting low-value waste into more valuable products and achieving a circular economy is a pressing challenge facing the world today. Coffee, as the world's most consumed non-alcoholic beverage, produces a large amount of biowaste such as coffee waste during its processing. These coffee wastes mainly exist in the form of coffee shells and coffee grounds. At present, most coffee wastes are not properly treated and effectively utilized.

[0003] Blending coffee waste with polymer materials to prepare coffee waste polymer composites is a feasible and environmentally friendly way of recycling. However, due to the performance problems of coffee waste polymer composites, the amount of coffee waste added to the coffee waste polymer composites currently used on the market is relatively small, which limits the efficiency of resource recycling of coffee waste. In order to reduce the waste of coffee waste, improve the recycling efficiency of coffee waste, and further reduce costs, it is of great practical significance to appropriately increase the proportion of coffee waste added to the composite material while ensuring the necessary performance of the composite material.

[0004] Since coffee grounds contain more organic groups, they tend to stick or agglomerate during processing. In addition, coffee grounds are porous and prone to stress concentration in their products, resulting in reduced toughness of the composite material or product failure. Therefore, it is necessary to pretreat coffee grounds to improve the mechanical properties of coffee waste polymer composites and products prepared therefrom.

[0005] In view of the application needs of coffee waste polymer composite products, the present invention needs to pre-treat the cellulose, hemicellulose, lignin, and oils contained in the coffee grounds, and bleach the coffee grounds, so as to prepare coffee waste polymer composite materials that meet the requirements of composite materials in various colors, mechanical properties, washing resistance, high temperature oil release performance, etc. Or at least provide the public with an alternative solution. Summary of the invention

[0006] A first aspect of the present invention relates to a method for treating coffee waste, the method comprising the steps of treating coffee grounds: (i) mixing the coffee grounds with hydrogen peroxide under alkaline conditions to form a first mixture; and (ii) obtaining treated coffee grounds through a separation process.

[0007] Preferably, in step (i), the alkaline condition is a pH value of 8-10. More preferably, the alkaline condition is maintained at a pH value of 8-10 by adding an alkaline solution.

[0008] In one embodiment, in the mixing in step (i), the weight ratio of the coffee grounds to hydrogen peroxide is 1:0.125 to 1:3.

[0009] Preferably, before step (i), the coffee grounds are mixed with an alkaline solution.

[0010] In one embodiment, the alkaline solution is a mixture of an alkaline material and water, wherein the alkaline material can be selected from sodium hydroxide, potassium hydroxide, calcium hydroxide or a combination thereof.

[0011] In one embodiment, in step (i), the concentration of hydrogen peroxide during the mixing process is maintained at 3%-15% by weight.

[0012] In one embodiment, in the mixing in step (i), the weight ratio of the coffee grounds to hydrogen peroxide is 1:0.125 to 1:5.

[0013] In one embodiment, step (i) includes the following steps: (a) mixing the coffee grounds with water to form a stirring liquid, wherein the weight ratio of the coffee grounds to water is 1:X; (b) adding the hydrogen peroxide to the stirring liquid at least once and mixing to form the first mixture, wherein the weight ratio of the hydrogen peroxide to the stirring liquid is 1:Y; (c) during the mixing in step (b), maintaining the alkaline condition by adding an alkaline solution.

[0014] In one embodiment, in step (a), the weight ratio of the coffee grounds to water is 1:3 to 1:10; in step (b), the hydrogen peroxide is added to the stirring liquid three times and mixed into the first mixture, in which the weight ratio of the hydrogen peroxide to the stirring liquid is 1:4 to 1:22, and during the mixing, the alkaline condition is maintained at a pH value of 8-10 by adding the alkaline solution.

[0015] In one embodiment, in step (a), the weight ratio of the coffee grounds to water is 1:3 to 1:10; in step (b), the hydrogen peroxide is added to the stirring liquid three times and mixed into the first mixture, in which the weight ratio of the hydrogen peroxide to the stirring liquid is 1:10, and during the mixing, the alkaline condition is maintained at a pH value of 8-9 by adding the alkaline solution.

[0016] In one embodiment, in step (a), the weight ratio of the coffee grounds to water is 1:3 to 1:10; in step (b), the hydrogen peroxide is added to the stirring liquid three times and mixed into the first mixture, in which the weight ratio of the hydrogen peroxide to the stirring liquid is 1:5 to 1:10, and during the mixing, the alkaline condition is maintained at a pH value of 8-10 by adding the alkaline solution.

[0017] In one embodiment, in step (a), the weight ratio of the coffee grounds to water is 1:3 to 1:10;

[0018] In step (b), the hydrogen peroxide is added to the stirring liquid three times and mixed into the first mixture, in which the weight ratio of the hydrogen peroxide to the stirring liquid is 1:5. During the mixing, the alkaline condition is maintained at a pH value of 8-9 by adding the alkaline solution.

[0019] In one embodiment, before step (ii), a flocculant solution is mixed with the first mixture to form a second mixture.

[0020] In one embodiment, before step (ii), a flocculant solution is mixed with the first mixture to form a second mixture. Preferably, the concentration of the flocculant in the flocculant solution is 0.05-3 wt %. More preferably, the concentration of the flocculant in the first mixture is 0.01-1 wt %.

[0021] In one embodiment, the flocculant solution is selected from organic flocculants, in particular starch, protein, gelatin, sodium alginate, sodium carboxymethyl cellulose, polyacrylamide, sodium polyacrylate, polyvinyl pyridine salt, polyethylene imine, or a combination thereof.

[0022] In one embodiment, the flocculant solution is selected from inorganic flocculants, in particular aluminum salts, iron salts, calcium chloride, potassium aluminum sulfate, aluminum chloride, iron sulfate, iron chloride, polyaluminum chloride, polyaluminum sulfate, activated silica, or a combination thereof.

[0023] In one embodiment, after forming the second mixture, the supernatant of the second mixture is removed; water is added, at least once, to the second mixture from which the supernatant has been removed and mixed, wherein the weight ratio of the water added to the coffee grounds is 3:1–20:1. Preferably, after forming the second mixture, the supernatant of the second mixture is removed; water is added, at least once, to the second mixture from which the supernatant has been removed and mixed, wherein the weight ratio of the water added to the coffee grounds is 5:1 to 3:1. More preferably, after forming the second mixture, the supernatant of the second mixture is removed; water is added, at least once, to the second mixture from which the supernatant has been removed and mixed, wherein the weight ratio of the water added to the coffee grounds is 3:1–20:1.

[0024] In one embodiment, before step (ii), the following steps are also included: mixing a flocculant solution with the first mixture to form a second mixture; after the second mixture is formed, removing the supernatant of the second mixture; adding, at least once, water to the second mixture from which the supernatant has been removed and mixing, wherein the weight ratio of the added water to the coffee grounds is 5:1 to 3:1; and waiting for 4-24 hours.

[0025] In one embodiment, before step (ii), the following steps are also included: mixing the flocculant solution with the first mixture to form a second mixture; after the second mixture is formed, removing the supernatant of the second mixture; adding, at least once, water to the second mixture from which the supernatant has been removed and mixing, wherein the weight ratio of the added water to the coffee grounds is 5:1 to 3:1; and waiting for 1 hour.

[0026] In one embodiment, the method further comprises the step of treating the coffee husks: (a) mixing the coffee husks with water at a weight ratio of 1:3 to 1:20 under heating; and (b) obtaining the treated coffee husks through a separation process.

[0027] In one embodiment, the coffee husks and water are mixed under heating at a weight ratio of 1:5 to 1:10. Preferably, the coffee husks and water are mixed at 70-100° C. for 2 hours.

[0028] In one embodiment, the coffee shells are mixed with water at 80-90° C. for 2 hours; the supernatant is removed; and the obtained coffee shells are mixed with water at 80-90° C. for 2 hours, wherein the weight ratio of the coffee shells to water is 1:3 to 1:5.

[0029] A second aspect of the present invention relates to a coffee waste polymer composite material comprising coffee grounds treated by the method according to any one of claims 1-28 and / or comprising coffee husks treated by the method according to any one of claims 29-32.

[0030] In one embodiment, the polymer is polypropylene.

[0031] In one embodiment, the composite material includes: polypropylene, polyolefin elastomer, the coffee grounds, and the coffee shells.

[0032] In one embodiment, the composite material further includes a toughening agent and / or an antioxidant.

[0033] In one embodiment, the polyolefin elastomer is maleic anhydride grafted polypropylene.

[0034] In one embodiment, the composite material further comprises titanium dioxide.

[0035] A third aspect of the present invention relates to a method for making a coffee waste polymer composite material, which comprises the following steps: (i) treating coffee grounds according to the method according to any one of claims 1 to 28; (ii) treating coffee husks according to the method according to any one of claims 29 to 32; (iii) mixing the coffee grounds with polypropylene and polyolefin elastomer to form a mixed material; and (iv) adding the mixed material to a feeder to form the coffee waste polymer composite material.

[0036] In one embodiment, a toughening agent and / or an antioxidant and / or titanium dioxide are further added to form the mixed material.

[0037] In one embodiment, the polyolefin elastomer is maleic anhydride grafted polypropylene. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Various exemplary embodiments of the present invention will be described in detail based on the following drawings, in which:

[0039] Figure 1 Soak the coffee husks at room temperature for 48 hours;

[0040] Figure 2 The color changes of the supernatant after boiling coffee husks for different times;

[0041] Figure 3A Unprocessed coffee grounds;

[0042] Figure 3B Coffee grounds treated by process 1;

[0043] Figure 3C Coffee grounds treated by process 2;

[0044] Figure 3D Coffee grounds treated by process 3;

[0045] Figure 3E Coffee grounds treated by process 4;

[0046] Figure 3F Coffee grounds treated by process 5;

[0047] Figure 3G Coffee grounds treated by process 5 (the left side of the figure is Example 3; the middle is Example 4; the right side is Example 5);

[0048] Figure 4A Boiling test results of coffee waste polymer composites made from untreated coffee grounds;

[0049] Figure 4B Boiling test results of coffee waste polymer composites made from coffee grounds treated by process 1;

[0050] Figure 4C Boiling test results of coffee waste polymer composites made from coffee grounds treated by process 2;

[0051] Figure 4D Boiling test results of coffee waste polymer composites made from coffee grounds treated by process 3;

[0052] Figure 4E Boiling test results of coffee waste polymer composites made from coffee grounds treated by process 4;

[0053] Figure 4F Boiling test results of coffee waste polymer composites made from coffee grounds treated by process 5;

[0054] Figure 4G Boiling test results of the coffee waste polymer composite material made from coffee grounds of Example 4;

[0055] Figure 4H The results of the boiling test of the coffee waste polymer composite material made from coffee grounds of Example 5;

[0056] Figure 5A High temperature oil release test results of coffee waste polymer composites made from untreated coffee grounds;

[0057] Figure 5B High temperature oil release test results of coffee waste polymer composites made from coffee grounds treated by process 1;

[0058] Figure 5CHigh temperature oil release test results of coffee waste polymer composites made from coffee grounds treated by process 2;

[0059] Figure 5D High temperature oil release test results of coffee waste polymer composites made from coffee grounds treated by process 3;

[0060] Figure 5E High temperature oil release test results of coffee waste polymer composites made from coffee grounds treated by process 4;

[0061] Fig. 5F High temperature oil release test results of coffee waste polymer composites made from coffee grounds treated by process 5;

[0062] Figure 5G High temperature oil release test results of the coffee waste polymer composites made from coffee grounds of Example 4 and Example 5;

[0063] Figure 6 Process 2 - Slurry without flocculant (left), slurry with flocculant and settling for 4 hours

[0064] (middle), and slurry after addition of flocculant and settling for 24 hours (right);

[0065] Fig. 7A TGA test results of coffee grounds after treatment by process 4 and process 5;

[0066] Figure 7B TGA test results of coffee grounds after treatment in Example 3-5;

[0067] Figure 8 Coffee grounds of different brands (before being treated by the process of the present invention);

[0068] Fig. 9 Coffee grounds of different brands (after being processed by process 4 of the present invention);

[0069] Fig.10 Coffee waste polymer composite granules made from coffee grounds treated by process 4;

[0070] Fig.11 Coffee waste polymer composite specimens made from coffee grounds treated by process 4;

[0071] Fig.12 Coffee waste polymer composite granules (added with TiO2) made from coffee grounds treated by Process 4; and

[0072] Fig.13 Coffee waste polymer composite specimens made from coffee grounds treated by process 4 (with added TiO2). DETAILED DESCRIPTION

[0073] The composite material of the present invention can be understood as comprising coffee waste treated by the present invention and a polymer. Unless otherwise specified, the percentages herein are by weight. For the convenience of describing the present invention, polypropylene will be used as an example of a polymer herein. However, this should be understood as not limiting the embodiments of the present invention.

[0074] Unless otherwise specified, the raw materials and chemicals used in this article do not require special treatment before use. The main raw materials and reagents are as follows:

[0075] Coffee grounds (SCG), brands A, B, C, and D;

[0076] Polypropylene (PP);

[0077] Toughening agent;

[0078] Maleic anhydride grafted polypropylene (MAPP);

[0079] Sodium hydroxide;

[0080] 50% hydrogen peroxide (H2O2);

[0081] Polyacrylamide;

[0082] Antioxidants;

[0083] Antioxidant.

[0084] The materials used in this article will be configured in the following way:

[0085] Prepare 1% sodium hydroxide solution

[0086] Dissolve 1 kg of sodium hydroxide in 99 kg of water and stir until it is completely dissolved.

[0087] Prepare 50% sodium hydroxide solution

[0088] Dissolve 1 kg of sodium hydroxide in 1 kg of water and stir until it is completely dissolved.

[0089] ·Prepare flocculant solution

[0090] Dissolve less than 50 grams of flocculant in 1 kg of water and stir until it is completely dissolved.

[0091] The tests and characterizations disclosed herein are described as follows:

[0092] Melt index test

[0093] The melt flow rate tester was used to test according to ISO1133, with a test load of 2.16 kg and a temperature of 230°C.

[0094] Density test

[0095] Tested according to ISO1183.

[0096] Tensile performance test

[0097] According to ISO527 test, the tensile rate used in the experiment is 50mm / min.

[0098] Bending performance test

[0099] According to ISO178 test, the tensile rate used in the experiment is 2mm / min.

[0100] Izod notched impact performance

[0101] According to ISO180 test, the downward swing energy of the experimental pendulum is 2.75J.

[0102] Boiling test

[0103] Place the specimen in a beaker and add enough water to completely immerse the specimen in the water. After boiling for 6 hours, take out the sample, wipe off the moisture on the surface of the specimen, observe the sample surface with an optical microscope, and compare it with the specimen before boiling and after drying.

[0104] High temperature oil test

[0105] Place the sample in an oven at 80°C or 150°C, and observe the surface condition of the sample after baking for a certain period of time.

[0106] Color test

[0107] The CIE1976L*a*b* color system is used to directly measure the lightness value (L) and two chromaticity coordinates (a and b). The L value represents black and white, and the range is 0-

[0108] 100, 0 is black, 100 is white; the a value represents red and green, positive value is red, negative value is green; the b value represents yellow and blue, positive value is yellow, negative value is blue.

[0109] Effect of coffee grounds and coffee shell processing on the properties of composite materials

[0110] Coffee husk processing

[0111] Coffee shells are an important component of the composite material of the present invention, and their morphology and properties have a great influence on the comprehensive properties of the composite material. After the coffee shells are soaked in water at room temperature (solid-liquid weight ratio 1:10, such as 1 kg of coffee shells to 10 kg of water) for 36-48 hours, Figure 1As shown in the figure, the supernatant is dark brown in color, and more substances are dissolved from the coffee shells by water. From the experimental results, it is inferred that there are still untreated soluble and color-developing substances in the coffee shells that are easily precipitated by water. Considering that this substance will affect the washing resistance test results in the composite material, the coffee shells must be treated.

[0112] Example 1

[0113] The coffee husks were boiled in water at a solid-liquid weight ratio of 1:10, and the water was changed every several hours. Figure 2 The color of the supernatant after boiling for different times (from left to right, the longer the boiling time. The far right is the control group). By comparison, it can be found that the color of the supernatant becomes lighter after boiling for 4 hours (i.e. Figure 2 The first and third bottles on the left in the middle indicate that the coffee shell precipitate is greatly reduced.

[0114] Considering the operability and cost of large-scale production, after optimization, the coffee husks were treated by boiling water for 4 hours (changing the water every 2 hours) with a solid-liquid weight ratio of 1:5. In Example 1, the coffee husk treatment process is shown in Table 1 below.

[0115] Table 1 Coffee shell processing technology

[0116]

[0117] Coffee grounds treatment

[0118] The following different embodiments will explain the process of treating coffee grounds according to the present invention.

[0119] No coffee grounds treatment process

[0120] Example 2

[0121] In order to improve the effect of coffee grounds treatment, the coffee grounds are initially crushed before being processed. The specific process of coffee grounds treatment is shown in the following table.

[0122] from Figure 3A As shown in FIG, the color of untreated coffee grounds is black.

[0123] The untreated coffee grounds were used to prepare the coffee waste polymer composite material and then injection molded. The specimens were then subjected to water boiling test and high temperature oil discharge test. The test results are as follows: Figure 4A and Figure 5A shown.

[0124] from Figure 4A It can be seen that the performance of the samples before and after the boiling test is basically the same. After drying for 18 hours, the color of the samples became slightly lighter than before boiling.

[0125] from Figure 5A It can be seen that after high temperature treatment, the splines showed obvious oil leakage, and there is room for improvement.

[0126] Coffee grounds processing technology 1

[0127] The coffee grounds were processed by treatment process 1 as shown in the following table.

[0128] Table 2 Coffee grounds treatment process 1

[0129]

[0130]

[0131] As can be seen from the above table, the total processing time of process 1 is about 92 hours, and the coffee grounds yield is about 48%.

[0132] Those skilled in the art should understand that the process in the above table is only an example, and all parameters in the table should not be interpreted as limiting the present invention. For example, the stirring speed of 700 rpm in the sodium hydroxide treatment is only an example, and can be adjusted according to actual operation as long as the stirring effect is guaranteed. The stirring time is generally 1-24 hours.

[0133] from Figure 3B As shown in the figure, after being treated by process 1, the color of the coffee grounds becomes significantly lighter and becomes light yellow.

[0134] The coffee waste polymer composites were prepared by the coffee grounds treated according to process 1 and then injection molded. The samples were then subjected to water boiling test and high temperature oil discharge test. The test results are shown in Figure 4B and Figure 5B shown.

[0135] from Figure 4B It can be seen that the performance of the samples before and after the boiling test is basically the same. After drying for 18 hours, the color of the samples became slightly lighter than before boiling.

[0136] like Figure 5B As shown in the figure, after high temperature treatment, the coffee waste polymer composite material in process 1 did not show oil leakage. This should be related to the removal of oily substances contained in coffee grounds during the treatment process in process 1.

[0137] In summary, after being treated by process 1, the color of coffee grounds and the oil emission problem of the composite material were significantly improved.

[0138] However, since cellulose and other substances in coffee grounds are prone to swelling under alkaline conditions, it is difficult to separate the coffee grounds from the slurry during the treatment of the coffee grounds according to process 1. The centrifugation step takes about 8 hours to treat 1 kg of coffee grounds according to process 1, and the separation of the coffee grounds is difficult and is not suitable for large-scale production.

[0139] In order to reduce the difficulty of production and improve production efficiency, the present invention optimizes the coffee grounds processing process by adding a flocculant to the coffee grounds processing process 2 based on the process 1.

[0140] Coffee grounds processing technology 2

[0141] The coffee grounds were processed by treatment process 2 as shown in the following table.

[0142] Table 3 Coffee grounds treatment process 2

[0143]

[0144]

[0145] As can be seen from the above table, the total processing time of process 2 is about 109 hours, and the coffee grounds yield is about 65%.

[0146] The flocculant used in process 2 is an organic flocculant, which mainly relies on the "bridging" effect to aggregate two or more dispersed phase particles together to produce flocculent precipitation. After the flocculant is added to the slurry, a significant sedimentation effect will appear. After 4 hours, the slurry will be clearly stratified, and after 24 hours, the supernatant will be clear. Figure 6 After adding flocculants for sedimentation, the centrifugation step in the process of treating 1 kg of coffee grounds only takes about half an hour, the difficulty of coffee grounds treatment is greatly reduced, and the total time for coffee grounds treatment is about 109 hours. At the same time, the coffee grounds yield is increased from 48% to 65%.

[0147] See Figure 3B and 3C By comparison, it can be seen that there is no significant difference in the color of the treated coffee grounds whether or not flocculants are added.

[0148] In the first embodiment, the flocculant used can be an inorganic flocculant or an organic flocculant. Common inorganic flocculants include aluminum salts, iron salts, calcium chloride, potassium aluminum sulfate (alum), aluminum chloride, iron sulfate, iron chloride, polyaluminum chloride, polyaluminum sulfate, activated silica, or a combination thereof.

[0149] Commonly used organic flocculants include starch, protein, animal glue, sodium alginate, sodium carboxymethyl cellulose, polyacrylamide, sodium polyacrylate, polyvinyl pyridine salt, polyethylene imine, or a combination thereof.

[0150] According to the experimental results, the total concentration of the flocculant in the coffee grounds slurry is recommended to be controlled at 0.01%-1%.

[0151] The coffee waste polymer composites were prepared by the coffee grounds treated in process 2 and then injection molded. The samples were then subjected to water boiling test and high temperature oil discharge test. The test results are shown in Figure 2. Figure 4C and Figure 5C shown.

[0152] from Figure 4C It can be seen that compared with process 1, the color change of coffee waste polymer composites treated by process 2 before and after the boiling test is relatively small.

[0153] like Figure 5C As shown, after high temperature treatment, the coffee waste polymer composite material in process 1 did not show oil leakage.

[0154] In summary, after being processed by process 2, the coffee grounds treatment process is simplified to a certain extent, and the treatment effect is better than that of process 1.

[0155] Considering that the processing time of process 2 is about 109 hours, the production cycle is long and the time cost is relatively high. In order to improve production efficiency and reduce production costs, the present invention intends to optimize the coffee grounds processing time and shorten the alkali treatment and H2O2 treatment standing time. At the same time, in order to ensure the deoiling and decolorization effect of coffee grounds, the present invention optimizes the coffee grounds processing process 3 by adding a water washing step on the basis of process 2.

[0156] Coffee residue treatment process 3

[0157] The coffee grounds were processed by treatment process 3 as shown in the following table.

[0158] Table 4 Coffee grounds treatment process 3

[0159]

[0160] Compared with process 2, the total time of coffee grounds processing in process 3 was reduced from 109 hours to 82 hours, and the coffee grounds yield was reduced from 65% to 47.6%.

[0161] Compared with coffee grounds processing process 3, coffee grounds processed in process 2 have a darker color (see Figure 3C , 3D This is mainly related to the shortened H2O2 treatment time and insufficient H2O2 reaction in process 2.

[0162] According to the experimental results, during the water washing process, the solid-liquid ratio is 1:3-1:20, the stirring time can be adjusted within the range of 10min-4h depending on actual needs, and the standing time can be adjusted within the range of 4h-24h depending on actual needs.

[0163] The coffee waste polymer composites were prepared by the coffee grounds treated according to process 3 and then injection molded. The samples were then subjected to water boiling test and high temperature oil discharge test. The test results are shown in Figure 4D and Figure 5D shown.

[0164] from Figure 4D It can be seen that the color change before and after the boiling test of process 3 is relatively small.

[0165] like Figure 5D As shown, there is no obvious change in the composite sample after the high temperature oil discharge test.

[0166] In summary, the treatment time of process 3 is significantly shortened compared with process 2, but the decolorization effect is not significantly changed. Therefore, in order to improve the decolorization effect of coffee grounds, the present invention optimizes the addition method of H2O2 during the H2O2 treatment process on the basis of process 3 to improve the reaction activity of H2O2, reduce the ineffective decomposition of H2O2, and improve the bleaching effect of H2O2. To this end, the present invention has formulated coffee grounds treatment process 4.

[0167] Coffee grounds processing technology 4

[0168] The coffee grounds were treated by treatment process 4, as shown in the following table. Different from the previous process, considering that the solution was always alkaline during the optimized H2O2 treatment process, in order to optimize the coffee grounds treatment time, the coffee grounds alkaline treatment process was removed in process 4, that is, the sodium hydroxide treatment in Table 2-4.

[0169] Table 5 Coffee grounds treatment process 4

[0170]

[0171]

[0172] In coffee grounds treatment process 4, during the H2O2 treatment process, H2O2 was added to the mixed solution three times.

[0173] To ensure the reactivity of H2O2, in coffee grounds treatment process 4, the pH value of the solution was adjusted every 10 minutes (controlled at 8-10).

[0174] At the same time, in order to ensure the deoiling and decolorizing effect of the coffee grounds, further reduce the residual H2O2 content in the coffee grounds before drying, and eliminate the hidden dangers in the drying process, a second water washing step is added during the coffee grounds processing.

[0175] According to the experimental results, in each washing process, the solid-liquid ratio is recommended to be 1:3-1:20, the stirring time can be adjusted within the range of 10 minutes to 4 hours depending on actual needs, and the standing time can be adjusted within the range of 4 hours to 24 hours depending on actual needs.

[0176] In addition, according to actual industrial production conditions, since the unprocessed coffee grounds have a high oil content, they are prone to agglomeration during the crushing process and are therefore difficult to crush. Therefore, in response to actual needs, the crushing step before the coffee grounds are processed can be selectively removed.

[0177] The coffee grounds processing time in process 4 is slightly reduced compared to process 3, from 82 hours to 78 hours, and the coffee grounds yield is basically the same, both around 50%.

[0178] Compared with coffee grounds treatment process 4, coffee grounds treatment process 3 has a more obvious improvement in color. Figure 3D , 3E . This is mainly due to the optimization of the H2O2 treatment process and the increase in the number of water washings. H2O2 generally has poor reaction activity in an acidic environment, but has good reaction activity in an alkaline environment and a better bleaching effect. The pH value of the solution was not adjusted during the process 3. As the reaction proceeded, the pH value of the solution continued to decrease, and the activity of H2O2 also continued to decrease, which led to a poorer decolorization effect of the coffee grounds than that of process 4. In addition, increasing the number of water washings is also conducive to further removing the color-developing substances soluble in water in the coffee grounds.

[0179] The coffee waste polymer composites were prepared by the coffee grounds treated according to process 4 and then injection molded. The samples were then subjected to water boiling test and high temperature oil discharge test. The test results are shown in Figure 4E and Figure 5E shown.

[0180] like Figure 4E As shown, the color change before and after the boiling test of process 4 is relatively small.

[0181] like Figure 5E As shown, there is no obvious change in the composite sample after the high temperature oil discharge test.

[0182] In summary, the processing time of process 4 is slightly shorter than that of process 3, and the decolorization effect of coffee grounds is significantly improved. In order to save production costs and realize the industrial production of coffee grounds processing, the present invention intends to further shorten the coffee grounds processing time by reducing the time of H2O2 processing, flocculation and water washing processes. At the same time, in order to ensure the deoiling and decolorization effect during the coffee grounds processing, the H2O2 processing is further optimized. Based on process 4, the present application intends to adjust the pH adjustment time interval from 10 minutes to 5 minutes, that is, to formulate coffee grounds processing process 5.

[0183] Coffee grounds processing technology 5

[0184] The coffee grounds were processed by treatment process 5 as shown in the following table.

[0185] Table 6 Coffee grounds treatment process 5

[0186]

[0187] In the coffee grounds treatment process 5, during the H2O2 treatment process, H2O2 is also added to the mixed solution three times. To ensure the reaction activity of H2O2, in the coffee grounds treatment process 5, the pH value of the solution is adjusted every 5 minutes (controlled at 8-10). Preferably, the interval time for adjusting the pH value of the solution can be adjusted according to the actual situation. More preferably, industrial operations can be controlled in real time by instruments to control the pH value to be stable in a range, such as pH10, to provide the necessary alkaline environment.

[0188] Compared with process 4, process 5 significantly reduces the processing time of coffee grounds from 78 hours to 22 hours, greatly improves production efficiency, and further reduces production costs. At the same time, the yield of coffee grounds is basically the same, both at around 50%. Figure 3E and 3F As shown, the color of the coffee grounds after process 5 becomes lighter.

[0189] The coffee waste polymer composites were prepared by the coffee grounds treated according to process 5 and then injection molded. The samples were then subjected to water boiling test and high temperature oil discharge test. The test results are shown in Figure 2. Figure 4F and Fig. 5F shown.

[0190] like Figure 4F As shown in Figure 5, the color change before and after the water boiling test of process 5 is relatively small, and the composite material sample does not show obvious changes after the high-temperature oil discharge test, such as Fig. 5F .

[0191] To further confirm the difference between the coffee grounds after the two processes, thermogravimetric analysis (TGA) was performed on the two coffee grounds. Fig. 7A The results showed that there was no significant difference in the TGA test results of the two.

[0192] In order to further save production costs, reduce the amount of wastewater generated during the coffee grounds treatment process, and improve the industrial production efficiency of coffee grounds treatment, the present invention further optimizes the solid-liquid ratio of the H2O2 treatment process of the coffee grounds treatment process on the basis of process 5, and reduces the use of raw materials. At the same time, in order to improve the industrial production efficiency of coffee grounds treatment, the H2O2 treatment and water washing process are further shortened to optimize the coffee grounds treatment time.

[0193] Embodiment 3-5

[0194] Based on coffee grounds processing process 5, Examples 3, 4, and 5 were prepared. The difference between Examples 3-5 is the H2O2 treatment. For the convenience of description, the following content only focuses on the H2O2 treatment in Examples 3-5 and its total treatment time and yield.

[0195] In Example 3, a stirring tank was used to add 1 kg of 30%-50% H2O2 solution and 7-9 kg of water to every 1 kg of coffee grounds in three times, and stirred at 700 rpm for 5 hours (the pH of the mixed solution was adjusted to 8-10 with sodium hydroxide solution every 5 minutes). Total treatment time: 22 hours.

[0196] In Example 4, a stirring tank was used, 1 kg of 30-50% H2O2 solution and 2-4 kg of water were added to 1 kg of coffee grounds in three times, and stirred at 700 rpm for 5 hours (the pH of the mixed solution was adjusted to 8-10 with NaOH solution every 5 minutes). Total treatment time: 19 hours.

[0197] In Example 5, a stirring tank was used to add 0.3-0.5 kg of H2O2 solution and 2.5-4.5 kg of water to every 1 kg of coffee grounds in three times, and stirred at 700 rpm for 5 hours (the pH of the mixed solution was adjusted to 8-10 with NaOH solution every 5 minutes). Total treatment time: 19 hours

[0198] Compared with Example 3, the coffee grounds treatment time of Example 4 and Example 5 is slightly reduced from 22 hours to 19 hours, and the solid-liquid ratio of the H2O2 treatment process is reduced from 1:10 to 1:5. At the same time, the amount of wastewater generated and the production cost are further reduced. In addition, the coffee grounds yield is basically the same as that of Example 3, both of which are about 50%.

[0199] The color of the coffee grounds after treatment in Example 3-5 is as follows Figure 3G Compared with Example 3, the color of the coffee grounds after Example 4 treatment becomes lighter, while the color of the coffee grounds after Example 5 treatment is relatively darker, which should be related to the amount of H2O2 added and the concentration of H2O2 during the H2O2 treatment process. In order to further confirm the difference between the coffee grounds after the two processes, the coffee grounds of Examples 3-5 were subjected to TGA test (as shown in Figure 2). Figure 7B ). The results show that compared with Example 3, the thermal stability of Examples 4 and 5 is reduced, which should be related to the amount and concentration of H2O2 used in the coffee grounds treatment process. As the amount and concentration of H2O2 increase, the degree of oxidation of each component in the coffee grounds treatment process becomes higher and higher, and the thermal stability of the coffee grounds decreases accordingly.

[0200] like Figure 4G-4H As shown, similar to Example 3, the color changes of the composite materials of Examples 4 and 5 before and after the water boiling test were not obvious.

[0201] like Figure 5G As shown, there is no obvious change in the composite sample after the high temperature oil discharge test.

[0202] Composite material performance testing

[0203] First, the coffee grounds and coffee shells treated by different processes were dried in an oven at 105°C for 2 hours, and then the dried coffee grounds, coffee shells, PP, MAPP, antioxidants, etc. were weighed and mixed evenly according to the experimental formula in Table 7. Subsequently, the mixture was added to a twin-screw extruder with a feeding frequency of 20 Hz and a main engine speed of 20 Hz for melt mixing, and the coffee waste polymer composite particles were prepared through processes such as water cooling and pelletizing.

[0204] Table 7 Experimental formula of coffee waste polymer composites

[0205]

[0206] The particles were added into the injection molding machine and injection molded into standard specimens. The mechanical properties of the composite materials of coffee grounds treated by different processes are shown in Table 8.

[0207] Table 8 Mechanical properties of coffee waste polymer composites

[0208]

[0209] As can be seen from the above table, the tensile strength, flexural modulus and impact resistance of the four materials are basically equivalent. Compared with other processes, the time required for the coffee grounds to be processed in Example 5 is shorter, only 19 hours, and the coffee grounds after treatment have higher thermal stability and lower processing costs. Although the color of the coffee grounds obtained after the treatment in Example 5 is darker than that of Example 4 and Example 4, the visual difference in the color of the prepared composite material is not obvious. At the same time, no abnormalities were found in the composite material boiling test and high-temperature oil discharge test. Taking all factors into consideration, Example 5 is a relatively superior coffee grounds processing process.

[0210] It can be seen from Table 8 that the physical properties of the coffee waste polymer composite material No. 3C# can meet the mechanical performance requirements of the composite material in terms of tensile strength and flexural modulus and are slightly higher than the mechanical performance requirements of the composite material, while the impact resistance is relatively poor. Therefore, the performance of the coffee waste polymer composite material can be optimized by adding a toughening agent to meet the mechanical performance requirements of the composite material.

[0211] First, the coffee grounds and coffee shells treated in Example 5 were dried in an oven at 105°C for 2 hours, and then the dried coffee grounds, coffee shells, PP, POE, MAPP, antioxidants, etc. were weighed and mixed evenly according to the experimental formula in Table 9. The mixture was then added to a twin-screw extruder with a feeding frequency of 20 Hz and a main engine speed of 20 Hz for melt mixing, and coffee grounds PP composite material particles were prepared through water cooling, pelletizing and other processes. The particles were then added to an injection molding machine and injection molded into standard specimens. The mechanical properties of the prepared coffee grounds PP composite material are shown in Table 10.

[0212] Table 9 Experimental formula of coffee waste polymer composites

[0213]

[0214] The particles were added into an injection molding machine and injection molded into standard specimens. The mechanical properties of the prepared coffee waste polymer composites are shown in Table 10.

[0215] Table 10 Mechanical properties of coffee waste polymer composites

[0216]

[0217] As can be seen from the table above, the tensile strength and flexural modulus of the optimized coffee grounds PP composite material are slightly reduced, but both can meet the mechanical properties requirements of the composite material. In addition, the impact strength is significantly improved from 2.7kJ / m2 to 3.5kJ / m2. In summary, the optimized coffee grounds PP composite material can meet the mechanical properties requirements of the composite material.

[0218] Preparation of composite materials from coffee grounds from different sources

[0219] Since different batches of coffee grounds have different components or sources, the colors of coffee grounds after processing may be different between batches. In order to confirm the influence of coffee grounds of different colors on the color of the composite material and ensure the stability of the production process, the present invention intends to process coffee grounds from three different sources, namely brand B, brand C and brand D, according to process 4 and compare them with coffee grounds from brand A. Figure 8 and Fig. 9 shown.

[0220] Depend on Figure 8 and Fig. 9 It can be seen that the colors of coffee grounds from four different sources are obviously different after being processed by the same process. Among them, the coffee grounds of brand A and brand B are relatively darker in color after processing, while the colors of brand C and brand D are relatively lighter. This is related to the variety, composition and grinding process of coffee beans.

[0221] First, the processed coffee grounds and coffee shells from different sources were dried in an oven at 105°C for 2 hours, and then the dried coffee grounds, coffee shells, PP, MAPP, antioxidants, etc. were weighed and mixed evenly according to the experimental formula in Table 11. Subsequently, the mixture was added to a twin-screw extruder with a feeding frequency of 20 Hz and a main engine speed of 20 Hz for melt mixing, and was prepared into coffee waste polymer composite particles through water cooling, pelletizing and other processes. The particles were then added to an injection molding machine and injection molded into standard strips. The pellets and strips of the prepared coffee waste polymer composites were respectively as follows: Fig.10 and Fig.11 shown.

[0222] Table 11 Experimental formula of coffee waste polymer composites

[0223]

[0224]

[0225] from Fig.10 It can be seen that the coffee waste polymer composite pellets from different sources have slight visual differences, which are consistent with the color depth of the processed coffee grounds. The colors of the composite materials No. 2# and No. 6# are relatively dark, the colors of the composite materials No. 7# and No. 8# are relatively light, and the colors of the splines are basically close visually.

[0226] The coffee waste polymer composite material specimens from different sources were placed in a colorimeter for testing. The color data of the coffee waste polymer composite materials from different sources are shown in Table 12.

[0227] Table 12 Color data of coffee waste polymer composites

[0228] Serial number L a b ΔL Δa Δb ΔE 2# 27.52 2.50 2.77 / / / / 6# 27.23 2.43 2.70 -0.29 -0.08 -0.07 0.31 7# 28.64 2.74 3.35 1.12 0.24 0.58 1.28 8# 28.18 2.87 3.36 0.66 0.37 0.59 0.96

[0229] Note: L value represents black and white, 0 is black and 100 is white; a value represents red and green, positive value is red and negative value is green; b value represents yellow and blue, positive value is yellow and negative value is blue.

[0230] From the composite material color data in the above table, it can be seen that, consistent with the visual results, there is no obvious difference in the color of the coffee waste polymer composite specimens from different sources.

[0231] Preparation of light-colored coffee grounds composite materials

[0232] According to the present invention's need for preparing light-colored coffee waste polymer composites, the present invention proposes to add a certain amount of titanium dioxide (TiO2) to coffee waste polymer composites from different sources to further determine the effect of processed coffee grounds from different sources on the color of the light-colored composites.

[0233] First, the coffee grounds and coffee shells from different sources treated according to process 4 in Table 5 are dried in an oven at 105°C for 2 hours, and then the dried coffee grounds, coffee shells, polypropylene, MAPP, antioxidants, etc. are mixed with about 1-3% TiO2 by weight according to the formula in Table 12. The mixture is then added to a twin-screw extruder with a feeding frequency of 20 Hz and a main engine speed of 20 Hz for melt mixing, and is prepared into coffee grounds PP composite particles through processes such as water cooling and pelletizing. The particles are then added to an injection molding machine and injection molded into standard strips. The prepared coffee waste polymer composite pellets and strips are as shown Fig.12 and Fig.13 shown.

[0234] from Fig.12 It can be seen that the particle size and sample size of the coffee waste polymer composites from different sources are slightly different. The color of the processed coffee grounds is also consistent with that of the composite materials No. 9# and No. 10#, which are relatively darker, and the composite materials No. 11# and No. 12#, which are relatively lighter.

[0235] The coffee waste polymer composite material specimens from different sources were placed in a colorimeter for testing. The color data of the coffee waste polymer composite materials from different sources are shown in Table 13.

[0236] Table 13 Color data of coffee waste polymer composites

[0237] Serial number L a b ΔL Δa Δb ΔE 9# 57.51 5.69 13.41 / / / / 10# 58.03 5.41 13.40 0.52 -0.28 -0.02 0.59 11# 61.84 4.97 13.66 4.33 -0.73 0.25 4.39 12# 61.17 5.29 14.35 3.66 -0.40 0.94 3.79

[0238] Note: L value represents black and white, 0 is black and 100 is white; a value represents red and green, positive value is red and negative value is green; b value represents yellow and blue, positive value is yellow and negative value is blue.

[0239] From the color data of the composite materials in the table above, it can be seen that the color of the polymer composite materials made of coffee waste from different sources becomes lighter after adding TiO2, and the color difference between the composite materials becomes larger. It is recommended that in the future, when using coffee waste processed from different batches, the color consistency of the composite materials can be ensured by adjusting the color powder solution.

[0240] Through the above embodiments, the present invention discloses the process for optimizing the treatment of coffee husks and coffee grounds, the conditions involved, and the physical properties thereof. The alkali treatment of the present invention can not only convert type I cellulose in plant fibers into type II cellulose, but can also be used to remove hemicellulose. In addition, H2O2 reacts with OH- in an alkaline environment to generate H2O and OOH-, and OOH- has a bleaching effect. It can be seen from the above embodiments that the alkali treatment of the present invention can be used for coffee grounds of different brands. The present invention also discloses the process for preparing coffee waste polymer composite materials, the conditions involved, and the physical properties thereof. The present invention also discloses that the color consistency of the composite material can be adjusted through a color powder scheme.

[0241] However, it should be understood by those skilled in the art that the embodiments disclosed herein are only used to describe the present invention and should not be construed as limiting the present invention. For example, the compounds selected herein, the starting material concentration, the stirring speed temperature when the compounds are mixed, and the centrifugal speed can be adjusted according to the actual operation conditions. In particular, the amount of the compound added in the process is related to its starting material concentration. Therefore, the amount of the compound added and the concentration in the embodiments disclosed herein are only illustrative. It should be understood by those skilled in the art that the relative weight ratio and solid-liquid ratio between the compounds in the present disclosure are the focus of the present invention. For example, the sodium hydroxide used in this specification can be replaced by a series of alkaline compounds such as potassium hydroxide and calcium hydroxide; the mixing ratio of the sodium hydroxide solution and water used in this specification is 1%. However, it should be understood by those skilled in the art that the mixing ratio can be from 1% to 50%, or even higher to a saturated solution; the raw material preparation and drying process in the embodiments of this specification are carried out in an oven at 105°C. However, depending on the actual situation, the oven can be adjusted to different temperatures, such as: between 80-120°C. Preferably, the moisture content of the dried coffee grounds is controlled at <2%; in the water-boiling treatment of coffee shells in the embodiments of this specification, the treatment process is to add 5 kg of water to every 1 kg of coffee grounds, and heat to 80-90°C and stir at a speed of 500 rpm for 2 hours. However, depending on the actual situation, the weight ratio of coffee grounds to water is 1:3-1:20, and the temperature can be between 70-100°C. Those skilled in the art should understand that the rotation speed in the embodiment is only an example and should not be interpreted as limiting the present invention; and the centrifugation process in the embodiments of this specification can be replaced by filter pressing due to actual conditions. Any numerical value in the numerical range disclosed in the present invention can be used as the end value of another numerical range, and any numerical value in the numerical range can implement the present invention and should not be understood as the implementation of the present invention is limited to the numerical range disclosed herein.

[0242] Although the present invention has been described in conjunction with specific embodiments of the present invention, many substitutions, modifications and variations of these embodiments will be apparent to those of ordinary skill in the art based on the foregoing description. The embodiments of the present invention are intended to cover all such substitutions, modifications and variations that fall within the broad scope of the appended claims. Therefore, any omissions, modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the embodiments of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for treating coffee waste, the method comprising the steps of treating coffee grounds: (i) mixing coffee grounds with hydrogen peroxide under alkaline conditions to form a first mixture; (ii) The processed coffee grounds are obtained through a separation process.

2. The method according to claim 1, characterized in that In step (i), the alkaline condition is a pH value of 8-10.

3. The method according to claim 1, characterized in that In the mixing of step (i), the weight ratio of the coffee grounds to hydrogen peroxide is 1:0.125 to 1:

3.

4. The method according to claim 1, characterized in that Before step (i), the coffee grounds are mixed with an alkaline solution.

5. The method according to claim 4, characterized in that The alkaline solution is a mixture of an alkaline material and water, wherein the alkaline material can be selected from sodium hydroxide, potassium hydroxide, calcium hydroxide or a combination thereof.

6. The method according to claim 1, characterized in that The alkaline condition is to maintain the pH value at 8-10 by adding alkaline solution.

7. The method according to claim 6, characterized in that The alkaline solution is a mixture of an alkaline material and water, wherein the alkaline material can be selected from sodium hydroxide, potassium hydroxide, calcium hydroxide or a combination thereof.

8. The method according to claim 6, wherein the alkaline solution is a mixture of an alkaline material and water, and the alkaline material can be selected from sodium hydroxide, potassium hydroxide, calcium hydroxide or a combination thereof.

9. The method according to claim 1, characterized in that: In step (i), the concentration of hydrogen peroxide during the mixing process is maintained at 3% to 15% by weight.

10. The method according to claim 6, characterized in that In step (i), the concentration of hydrogen peroxide during the mixing process is maintained at 3% to 15% by weight.

11. The method according to claim 1, characterized in that: In the mixing of step (i), the weight ratio of the coffee grounds to hydrogen peroxide is 1:0.125 to 1:

5.

12. The method according to claim 1, characterized in that Step (i) comprises the following steps: (a) mixing the coffee grounds with water to form a stirring liquid, wherein the weight ratio of the coffee grounds to water is 1:X; (b) adding the hydrogen peroxide to the stirring liquid at least once and mixing them into the first mixture, wherein the weight ratio of the hydrogen peroxide to the stirring liquid is 1:Y in the first mixture; (c) during the mixing in step (b), maintaining the alkaline condition by adding an alkaline solution.

13. The method according to claim 12, characterized in that In step (a), the weight ratio of coffee grounds to water is 1:3 to 1:10; In step (b), the hydrogen peroxide is added to the stirring liquid three times and mixed into the first mixture, in which the weight ratio of the hydrogen peroxide to the stirring liquid is 1:4 to 1:

22. During the mixing, the alkaline condition is maintained at a pH value of 8-10 by adding the alkaline solution.

14. The method according to claim 12, characterized in that In step (a), the weight ratio of coffee grounds to water is 1:3 to 1:10; In step (b), the hydrogen peroxide is added to the stirring liquid three times and mixed into the first mixture, in which the weight ratio of the hydrogen peroxide to the stirring liquid is 1:

10. During the mixing, the alkaline condition is maintained at a pH value of 8-9 by adding the alkaline solution.

15. The method according to claim 12, characterized in that In step (a), the weight ratio of coffee grounds to water is 1:3 to 1:10; In step (b), the hydrogen peroxide is added to the stirring liquid three times and mixed into the first mixture, in which the weight ratio of the hydrogen peroxide to the stirring liquid is 1:5 to 1:

10. During the mixing, the alkaline condition is maintained at a pH value of 8-10 by adding the alkaline solution.

16. The method according to claim 12, characterized in that In step (a), the weight ratio of coffee grounds to water is 1:3 to 1:10; In step (b), the hydrogen peroxide is added to the stirring liquid three times and mixed into the first mixture, in which the weight ratio of the hydrogen peroxide to the stirring liquid is 1:

5. During the mixing, the alkaline condition is maintained at a pH value of 8-9 by adding the alkaline solution.

17. The method according to claim 1, wherein: Before step (ii), a flocculant solution is mixed with the first mixture to form a second mixture.

18. The method according to any one of claims 1 to 16, wherein: Before step (ii), a flocculant solution is mixed with the first mixture to form a second mixture.

19. The method according to claim 17, wherein: The concentration of the flocculant in the flocculant solution is 0.05-3% by weight.

20. The method according to claim 18, wherein: The concentration of the flocculant in the flocculant solution is 0.05-3% by weight.

21. The method according to claim 19 or 20, wherein: The concentration of the flocculant in the first mixture is 0.01-1% by weight.

22. The method according to claim 21, wherein: The flocculant solution is selected from organic flocculants, in particular starch, protein, animal glue, sodium alginate, sodium carboxymethyl cellulose, polyacrylamide, sodium polyacrylate, polyvinyl pyridine salt, polyethylene imine, or a combination thereof.

23. The method according to claim 21 or 22, wherein: The flocculant solution is selected from inorganic flocculants, in particular aluminum salts, iron salts, calcium chloride, potassium aluminum sulfate, aluminum chloride, iron sulfate, iron chloride, polyaluminum chloride, polyaluminum sulfate, activated silica, or a combination thereof.

24. The method of claim 17, wherein: After forming the second mixture, the supernatant of the second mixture is removed; water is added, at least once, to the second mixture from which the supernatant has been removed and mixed, wherein the weight ratio of the added water to the coffee grounds is 3:1-20:

1.

25. The method according to claim 24, wherein: After forming the second mixture, the supernatant of the second mixture is removed; water is added, at least once, to the second mixture from which the supernatant has been removed and mixed, wherein the weight ratio of the added water to the coffee grounds is 5:1 to 3:

1.

26. The method of claim 18, wherein: After forming the second mixture, the supernatant of the second mixture is removed; water is added, at least once, to the second mixture from which the supernatant has been removed and mixed, wherein the weight ratio of the added water to the coffee grounds is 3:1-20:

1.

27. The method of claim 13, wherein: Before step (ii), the method further includes the following steps: mixing a flocculant solution with the first mixture to form a second mixture; after forming the second mixture, removing the supernatant of the second mixture; adding, at least once, water to the second mixture from which the supernatant has been removed and mixing, wherein the weight ratio of the added water to the coffee grounds is 5:1 to 3:1; and waiting for 4-24 hours.

28. The method according to claim 14, 15 or 16, wherein: Before step (ii), the method further includes the following steps: mixing a flocculant solution with the first mixture to form a second mixture; after forming the second mixture, removing the supernatant of the second mixture; adding, at least once, water to the second mixture from which the supernatant has been removed and mixing, wherein the weight ratio of the added water to the coffee grounds is 5:1 to 3:1; and waiting for 1 hour.

29. The method according to claim 1 or 17 or 24, characterized in that: The method further comprises the step of treating the coffee husks: (a) mixing coffee husks with water in a weight ratio of 1:3 to 1:20 under heating; (b) The treated coffee husks are obtained through a separation process.

30. The method according to claim 29, characterized in that The coffee shells and water are mixed under heating at a weight ratio of 1:5 to 1:

10.

31. The method according to claim 30, characterized in that In step (a) of claim 29, the coffee husks are mixed with water at 70-100°C for 2 hours.

32. The method according to claim 31, characterized in that The coffee shells are mixed with water at 80-90° C. for 2 hours; the supernatant is removed; the obtained coffee shells are mixed with water at 80-90° C. for 2 hours, wherein the weight ratio of the coffee shells to water is 1:3 to 1:

5.

33. A coffee waste polymer composite comprising coffee grounds treated according to the method of any one of claims 1 to 28 and / or comprising coffee husks treated according to the method of any one of claims 29 to 32.

34. The composite material according to claim 33, characterized in that The polymer is polypropylene.

35. The composite material according to claim 33, characterized in that The composite material comprises: polypropylene, polyolefin elastomer, the coffee grounds, and the coffee shells.

36. The composite material according to claim 35, characterized in that The composite material further comprises a toughening agent and / or an antioxidant.

37. The composite material according to claim 35 or 36, characterized in that The polyolefin elastomer is maleic anhydride grafted polypropylene.

38. The composite material according to claim 35 or 36, characterized in that The composite material further comprises titanium dioxide.

39. A method for making a coffee waste polymer composite material comprising the following steps: (i) treating coffee grounds according to any one of claims 1 to 28; (ii) treating coffee husks according to any one of claims 29 to 32; (iii) mixing the coffee grounds, the coffee grounds with polypropylene and polyolefin elastomer to form a mixed material; and (iv) adding the mixed material to a feeder to form the coffee waste polymer composite material.

40. The method according to claim 39, wherein in step (iii) of claim 39, a toughening agent and / or an antioxidant and / or titanium dioxide are further added to form the mixed material.

41. The method according to claim 39 or 40, characterized in that The polyolefin elastomer is maleic anhydride grafted polypropylene.